Prevalence of Salmonella and Campylobacter from retail poultry in the Southeastern United States - Baca A., María V. (Zamorano: Escuela Agrícola Panamericana, 2025)
Chicken meat the most consumed poultry products in the USA and one the most asociated with foodborne illnesses. The objetive of this study was to analyse the prevalence of two common patogens in poultry products, Salmonella and Campylobacter, in retail poultry at the Southeastern United States. A total of 74 samples were collected from four different grocery stores. Sample types were selected based on availability, divided into breasts, wings, thighs, and tenders and categorically collected from conventional, antibiotic-free, organic and air-chilled productions. All samples originated from 14 different processing plants based on the different codes marked in each package. Conventional detection was employed using bacterial culturing on selective media, XLT4 and Campy Cefex Agar. Also, molecular methods Gene-Up for Salmonella (SLM2) (AOAC Official Method of Analysis 2020.02) and the 3M^TM Molecular Detection Assay 2 (MDS) for Salmonella and Camylobacter were applied to ensure accurate results. A prevalence of 13.5% for Salmonella (p = <0.0001) and 6.8% for Campylobacter (p = <0.0001), respectively, was determined. No differences were determined, but breasts and wings showed higher prevalences for both pathogens. The highest contamination was for conventional and antibiotic-free (ABF) productions for Salmonella while Campylobacter showed the opposite. In processing plants, the highest Salmonella prevalence was 42% and the lowest 0%, similar to Campylobacter with 40% and 0%. Results revealed that the presence of skin, location in the body, and potencially certain practices employed in chicken production or processing may have influenced contamiantion levels Reinforced sanitation protocols is important to reduce contamination to the lowest possible level.